A sabedoria socrática no ensino de filosofia - Souza, Francisco Jackson de Freitas (2024)
The objective of this research is to understand and analyze the wisdom of Socrates and his possible contributions to education with regard to the teaching-learning process, especially for the teaching of philosophy. From the reflection of certain practices used by Socrates such as “irony” and “maieutics”, we seek to evaluate how these postures can be useful in the classroom and how they can foster a school environment capable of producing teaching-learning where students can become increasingly active and protagonists in the construction of their own knowledge. Thus, the objective is to increase students' involvement with philosophy, in which they can perceive teaching capable of awakening awareness of their own reality, be it social, economic, emotional, psychological, etc., and experience a practical philosophy. The target audience is high school students, which does not mean that the activities, reflections and conclusions of this research cannot be used at other educational levels.